The Effect of Organizational Culture, Communication, Discipline and Work Motivation on Employee Performance in the National Land Agency of Labuhanbatu Regency - Efendi, Asrol; Lam'ah, Siti; Halim, Abd. (Budapest International Research and Critics University, 2022)
This study aims to analyzeorganizational culture, communication, discipline and work motivation on employee performance at the National Land Agency of Labuhanbatu Regency. This type of research is quantitative, the place of this research is the National Land Agency of Labuhanbatu Regency and a questionnaire using a Likert scale. The multiple linear regression equation of this study is: Y= (-6.790) +0.263X1+0.314X2 +0.657X3+0.312X4. The results of the regression analysis obtained the t-count value of 2.423 > t-table 1.66277 explaining that the Communication variable (X2) has a positive effect on the Employee Performance variable (Y). Then the significant value is 0.017 <0.05, which means that the Communication variable (X2) has a significant effect on the Employee Performance variable (Y). Then the results of the regression analysis obtained the t arithmetic value of 4.496 > t table 1.66277 indicating that the Discipline variable (X3) has a positive effect on the Employee Performance variable (Y). From these results it can be stated that Organizational Culture (X1), Communication (X2), Discipline (X3), and Work Motivation (X4) simultaneously have a positive and significant effect on Employee Performance (Y). The value of R Square from the analysis of the coefficient of determination of 0.588 means that Employee Performance can be explained by the variables of Organizational Culture, Communication, Discipline and Work Motivation of 58.8%, while the remaining 41.2% can be explained by other variables not examined in this study.